Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0229600
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of habitat loss on occupancy patterns of the eastern green lizard Lacerta viridis at the core and periphery of its distribution range

Abstract: The effects of habitat loss on the distribution of populations are often linked with species specialization degree. Specialist species can be more affected by changes in landscape structure and local patch characteristics compared to generalist species. Moreover, the spatial scale at which different land covers (eg. habitat, cropland, urban areas) affect specialist species can be smaller. Specialization is usually assumed as a constant trait along the distribution range of species. However, for several taxa, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Thermoregulation implies moving between sun and shade (Huey, 1974), and our results show that the two most important habitat variables are the presence of shrubs and trees in combination with grassland on a small scale, thus providing a mosaic of different ecological conditions. Our results confirm other findings that heterogeneous areas with bushy parts are most suitable for the species (Heltai et al, 2015;Prieto-Ramirez et al, 2018, 2020a. The results regarding microhabitat use show that shrubs and logs the most used features by lizards for basking and as shelter and/or hiding place, confirming other observations for the European Green lizard (Heltai et al, 2015), but also for related species L. bilineata (Luppi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Thermoregulation implies moving between sun and shade (Huey, 1974), and our results show that the two most important habitat variables are the presence of shrubs and trees in combination with grassland on a small scale, thus providing a mosaic of different ecological conditions. Our results confirm other findings that heterogeneous areas with bushy parts are most suitable for the species (Heltai et al, 2015;Prieto-Ramirez et al, 2018, 2020a. The results regarding microhabitat use show that shrubs and logs the most used features by lizards for basking and as shelter and/or hiding place, confirming other observations for the European Green lizard (Heltai et al, 2015), but also for related species L. bilineata (Luppi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The Italian dataset revealed that adults versus juveniles selected preferentially different bush species-dominated habitats for their activities. Although it is generally considered that for lizards (and reptiles in general), the actual plant species present are less important than the physical influence they create [55], in the case of green lizards, we demonstrated that plant species are very relevant, as they emerged as significant factors in the habitat use for males and females (Rubus sp.) as well as for juveniles (Spartium sp.).…”
Section: Conservation Considerationsmentioning
confidence: 68%
“…The comparative evidence from these studies shows that very local (habitat and climatic) conditions may strongly condition the ecological requirements of green lizards, and consequently that site-specific studies should always be carry out for a reliable management of the various L. bilineata populations. In this regard, in the closely-related Lacerta viridis, there was evidence of higher specialization degree in peripheral populations compared with populations in the core, with peripheral populations exhibiting a higher sensitivity to habitat loss, especially at small spatial scale [55]. Further studies should explore whether the same pattern occurs in L. bilineata populations.…”
Section: Conservation Considerationsmentioning
confidence: 91%
“…I applied a patchlandscape approach integrating landscape parameters across spatial scales with patch and within-patch parameters. Effects of habitat loss on occupancy patterns of L. viridis have recently been investigated in the same study system (Prieto-Ramírez et al, 2020), with occupancy being found to be mostly defined by landscape configuration, with the strongest effect of the overall habitat loss process occurring at the 750 m scale around patches. No negative effect of isolation was found, and at the patch level, occupancy depended on patches with both long perimeter and enough core area in the interior, indicating that the species uses not only the border but also the interior of patches.…”
Section: Introductionmentioning
confidence: 99%
“…is a robust combination of survey design types, solving mismatches between occupancy and abundance data gathering methods.Concerning the necessary conservation measures for L. viridis in the studied region,Prieto-Ramírez et al (2020) highlighted the importance of protecting and restoring riparian vegetation, which might be an important corridor connecting populations, to increase the occupancy probability of remnant patches. In addition to this recommendation, early conservation measures to avoid the decline of still extant populations of L. viridis should include ensuring enough patch interior area, restoring habitat at small scales (~50 m), at which cropland and urban areas are exerting strong negative pressure, and protecting and restoring habitat at large scales (~1.5 km), which cover the species' maximum dispersal distance and at which connectivity can be much more strengthened.Understanding the response of wild animal populations to habitat loss at different stages of the population extinction process, and at different spatial levels, is of vital importance to identify the best possible conservation measures.…”
mentioning
confidence: 99%